Effect of prey concentrations and feed training on production of Hoplias lacerdae juvenile - LUZ,RONALD K. (2015)
The aim of this work was to investigate the effects of daily prey concentration during the first 15 days of active feeding of Hoplias lacerdae larvae, and the juvenile size on the feed training. In the first phase, the larvae received five Artemia nauplii concentrations (P). In the second phase, the juveniles from each treatment were trained to accept formulated diet. Superior growth was related to higher initial daily prey concentrations (900 and 1100 nauplii larvae-1). During feed training, the growth tendency was similar to that verified in the first phase. The lowest values of specific growth rate (SGR) were registered after the introduction of the semi-moist diet used in the feed training. However, the values of SGR recovered along the experiment and similar rates were found among the treatments. Survival, mortality and cannibalism were similar in the different treatments at the end of both phases. It can be concluded that: the prey concentration affects growth of H. lacerdae during the first 15 days of active feeding, and feed training can be initialized with juveniles of about 16 mm of total length.